An Empirical Analysis of the Impact of Public Debt Management Strategies on Nigeria’s Debt Profile - Rafindadi, Abdulkadir Abdulrashid; Musa, Abdulazeez (International Journal of Economics and Financial Issues, 2019)
This study examined the impact of debt management strategies on the Nigeria’s public debt profile. Specifically, the study evaluates the impact of debt refinancing, and measure the impacts of debt forgiveness and debt conversion scheme on the public debt profile of Nigeria. To ensure robust result is achieved, time series data from World Development Index (WDI), Central Bank of Nigeria (CBN) and Debt Management office were used. The study applied the ARDL econometric methodology in order to investigate the long-run and the short run dynamics of total debt profile of the country on debt refinancing (DRF) debt forgiveness (DF) and Debt Conversion Scheme (DCV). The findings of the study reveal that debt refinancing has negative impact on total debt profile in Nigeria. In addition to that, debt forgiveness was detected to have significant negative impact on the debt profile of the country. While, Debt Conversion on its part was found to be having significant effect on the Nigeria’s debt profile. The implications of these findings is that whenever, the debt profile of the country is not streamlined with the tenets of economic development and fiscal policies of the country, then it is obvious that any persistent and sustained rise in exchange rate, devaluation and or fall in the country’s external reserve will add to existing economic hardship of the country, particularly when greeted by a fall in the international market prices of petroleum. These developments can overheat the economy, retard internal plans for economic expansion and cause significant derelictions of already attained economic growth. The researchers thereby, recommend that government should strengthen debt refinancing in order to reduce debt profile of the country, seek for debt forgiveness and provide more instruments for debt conversion with a view to drastically reduce the Nigeria’s national debt profile following its observed long run effect to the country’s economic wellbeing. Keywords: Debt Refinancing, Debt Forgiveness, Debt Conversion, Total Debt JEL Classifications: G3, M41 DOI: https://doi.org/10.32479/ijefi.7672